2022
DOI: 10.3390/molecules27175552
|View full text |Cite
|
Sign up to set email alerts
|

Dual Inhibition of HIV-1 and Cathepsin L Proteases by Sarcandra glabra

Abstract: The COVID-19 pandemic continues to impose a huge threat on human health due to rapid viral mutations. Thus, it is imperative to develop more potent antivirals with both prophylactic and treatment functions. In this study, we screened for potential antiviral compounds from Sarcandra glabra (SG) against Cathepsin L and HIV-1 proteases. A FRET assay was applied to investigate the inhibitory effects and UPLC-HRMS was employed to identify and quantify the bioactive components. Furthermore, molecular docking was car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…Inhibition of HIV-1, Cat L, and Renin PRs by SB Extracts SB extract was prepared from the whole plant according to a previously described method [20]. Using a high-throughput screening approach [20,21], the safety of four SB extracts (SBW, SB30, SB60, and SB85: prepared from water or MeOH-H 2 O) was initially evaluated using renin protease (Table 1) (Please refer to the Supplementary Materials for details). SBW and SB30 had anti-human renin PR activities with IC 50 values of 0.59 and 0.70 mg/mL, respectively, suggesting that these two extracts may present minor toxicity to humans.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Inhibition of HIV-1, Cat L, and Renin PRs by SB Extracts SB extract was prepared from the whole plant according to a previously described method [20]. Using a high-throughput screening approach [20,21], the safety of four SB extracts (SBW, SB30, SB60, and SB85: prepared from water or MeOH-H 2 O) was initially evaluated using renin protease (Table 1) (Please refer to the Supplementary Materials for details). SBW and SB30 had anti-human renin PR activities with IC 50 values of 0.59 and 0.70 mg/mL, respectively, suggesting that these two extracts may present minor toxicity to humans.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular docking was performed for the top four inhibitors (Scutellarein, Hispidulin, Apigenin, and Luteolin) against both HIV-1 PR and Cat L PR [21]. As shown in Table 4, the binding energies of Scutellarein, Hispidulin, Apigenin, and Luteolin were −46.959 to −38.811 kcal/mol towards Cat L PR, and −56.377 to −51.378 kcal/mol towards HIV-1 PR.…”
Section: Molecular Docking Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jin et al [ 80 ] reported that isofraxidin ( 230 ) effectively inhibited platelet aggregation through the PI3K/AKT and mitogen‑activated protein kinase (MAPK) pathways, thereby alleviating lung inflammation induced by influenza A. In the work by Pan et al [ 158 ], SGE was found to inhibit HIV-1 protease and cathepsin L with IC 50 values ranging from 0.003 to 0.07 mg/mL and 0.11 to 0.26 mg/mL, respectively. Notably, chlorogenic acid ( 377 ), a prominent constituent of the extract, displayed the most potent inhibitory activity against the two viral proteases.…”
Section: Biological Activitiesmentioning
confidence: 99%